Endometrial changes after methotrexate treatment: Relation with multiple nabothian cysts and future pregnancies. (August 2016) - Balaouras, Dimitrios; Chitzios, Dimitrios; Daniilidis, Angelos; Tantanasis, Theocharis; Mavromatidis, Georgios; Loufopoulos, Aristotelis; Nasioutziki, Maria; Asimakopoulos, Efstratios
A clinical study was conducted in order to validate the effect of methotrexate on 30 patients with ectopic pregnancy (EP). A typical ultrasound appearance of multiple cysts of Naboth in the cervix was observed on six cases that are studied below. Endometrial sample with endogyn was retrieved from the six cases after the treatment with methotrexate was complete. The cytological results were studied and there were many changes found in the endometrial cells, in their cores, and some inflammatory cells as well. Two out of the six cases studied show more profound evidence. The cellular appearance of the endometrium after the treatment is discussed, in relation to the presence of multiple Nabothian cysts, as a result of inflammatory reaction, and the possibility of any influence in the capacity for a future pregnancy.